Low-energy correlations in the positronium-hydrogen-atom system - Adhikari, Sadhan K. [UNESP] (Elsevier, 2001)
Employing a nonlocal model potential for electron exchange we study positronium-hydrogen-atom (Ps-H) scattering using a five-state coupled-channel model allowing for Ps(2s,2p)H(1s) and Ps(1s)H(2s,2p) excitations. We find remarkable correlations among S-wave Ps-H binding energy, scattering length, effective range, and resonance energy in the electronic singlet state. Using these correlations we predict fairly accurate values of singlet Ps-H scattering length (3.50a0) and effective range (1.65a0).